A Model of Integrated Multilevel Safety Intervention Practices in Malaysian Construction Industry. (2017) - Mohammad, Mazlina Zaira; Hadikusumo, Bonaventura H.W.
Abstract: Construction safety management improvement could be aligned with the condition at the workplace. The aim of this research is to identify the most significant safety practices at each intervention levels in improving behavioral safety performance of workers in the construction industry. A literature review was used to identify and determine the relevance of a list of safety intervention practices that take place at various levels; a total of 42 safety practices were identified. Questionnaires were then circulated to measure the level of significant each safety intervention practices towards a positive behavioral safety performance of workers. Targeted respondents are safety personnel and middle level personnel from construction companies that manage differ of construction projects such as oil and gas, infrastructure and building projects. The data will be collected at least from 430 respondents and will be analyzed using structural equation modelling (SEM) to determine the most significant safety practices at each intervention level. From the first result will be references to develop a dynamic model of integrated multilevel safety intervention practices in construction industry. Findings expected to be useful as a guidance in safety construction management in order to improve behavioral safety performance of multinational worker.